Jacobi script v sign-functions and discrete Fourier transforms - Ruzzi, M. [UNESP] (AIP Publishing, 2006)
Properties of the Jacobi script v sign3-function and its derivatives under discrete Fourier transforms are investigated, and several interesting results are obtained. The role of modulo N equivalence classes in the theory of script v sign-functions is stressed. An important conjecture is studied. © 2006 American Institute of Physics.